Parent/carer views on personal health budgets for disabled children who use rehabilitation therapy services. Issue 2 (7th February 2018) - Hutton, Eve; King, Annette
Abstract: Personalised budgets are promoted as the person-centred alternative to generically provided services. Nine parents/carers of disabled children (aged 18 years or younger) who accessed at least two rehabilitation therapy services (physiotherapy, occupational therapy, and speech and language therapy) were recruited from one region in England. Focus group/interviews explored their views on the proposed introduction of personalised budgets. Parents and carers viewed a personal health budget with caution and perceived benefits were tempered by their experiences of current provision. Concerns were raised about entitlement and how a personal budget would work in practice.